ACCESSIBILITY IN ACTION: EXAMINING VOCATIONAL EDUCATION PATHS FOR DISABLED LEARNERS IN CHINA - Jun , Huang Wei; Hua , Chen Li (Research Journal of Education and Allied Studies, 2024)
China is home to a substantial disabled population, with approximately 82.96 million individuals, representing about 6.34% of the nation's total population. The Outline of the National Medium- and Long-Term Education Reform and Development Plan (2010-2020) underscores the importance of promoting vocational education for people with disabilities, emphasizing the development of higher education opportunities for this segment of the population. It calls for enhanced provincial government coordination to facilitate the alignment of secondary and higher vocational education, fostering the coordinated growth and resource sharing of vocational education within each province. During the 12th Five-Year Plan period, secondary vocational education for individuals with disabilities witnessed a steady, upward trajectory. Concurrently, higher vocational education for this demographic advanced in parallel. The seamless connection between secondary and higher vocational education plays a pivotal role in the holistic development of vocational education for individuals with disabilities. This research investigates the linkage between secondary and higher vocational education for individuals with disabilities, with the aim of assessing the current state, identifying existing challenges, and providing valuable insights to facilitate the effective development of vocational education for this population.